Plasma apelin-12 levels may predict in-hospital major adverse cardiac events in ST-elevation myocardial infarction and the relationship between apelin-12 and the neutrophil/lymphocyte ratio in patients undergoing primary coronary intervention. (April 2017) - Topuz, Mustafa; Oz, Fahrettin; Akkus, Oguz; Sen, Omer; Topuz, Ayse Nur; Bulut, Atilla; Ozbicer, Suleyman; Okar, Sefa; Koc, Mevlut; Gur, Mustafa
Objective: We aimed to investigate the compliance of plasma apelin-12 levels to show angiographic properties and hospital MACE in patients with ST-elevation myocardial infarction (STEMI) undergoing primary percutaneous coronary intervention (PCI). Material and Methods: The association of apelin-12 levels with the N/L ratio on admission was assessed in 170 consecutive patients with primary STEMI undergoing primary PCI. All patient SYNTAX scores and thrombolysis in myocardial infarction (TIMI) flow grades were also assessed. Patients were divided into two groups according to their TIMI flow grade. Patients with a TIMI 0-2 flow and TIMI 3 flow with grade 0/1 myocardial blush grade (MBG) score were defined as the no-reflow group and patients with TIMI grade 3 flow with ⩾2 MBG were considered as the normal flow group. Results: Baseline apelin-12 levels were significantly lower in the no-reflow group than in the normal flow group (3.3±1.81 vs 6.2±1.74, p<0.001). In-hospital events, including death, myocardial infarction (MI) and re-infarction were significantly higher in patients in the no-reflow group than normal flow group (23% vs 7%, p<0.001). Apelin-12 level was negative correlated with the N/L ratio (r= -0.352, p<0.001), Hs-Crp (r=-0.272, p=0.01) and SYNTAX score (r= -0.246, p=0.029). In the multivariate regression analysis, apelin-12, presence of no-reflow and the SYNTAX score were independent predictors of in-hospital MACE (odds ratio [OR] 1.41, 95% confidence interval (CI) [1.27 to 1.67], p=0.001 for apelin-12, OR 1.085, [0.981 to 1.203], p<0.001 for no-reflow and OR 0.201, 95% CI [0.05 to 0.47], p= 0.004 for SYNTAX score). Conclusion: We have shown that lower apelin-12 level on admission is associated with higher SYNTAX scores and no-reflow phenomenon and may be used as a prognostic marker for hospital MACE in patients with STEMI.